2020
DOI: 10.1021/acs.nanolett.0c03994
|View full text |Cite
|
Sign up to set email alerts
|

Too Cool for Blackbody Radiation: Overbias Photon Emission in Ambient STM Due to Multielectron Processes

Abstract: Light emission from tunnel junctions are a potential photon source for nanophotonic applications. Surprisingly, the photons emitted can have energies exceeding the energy supplied to the electrons by the bias. Three mechanisms for generating these so-called overbias photons have been proposed, but the relationship between these mechanisms has not been clarified. In this work, we argue that multielectron processes provide the best framework for understanding overbias light emission in tunnel junctions. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 45 publications
2
40
0
Order By: Relevance
“…These two peaks are not present (or cannot be distinguished from the background) in the spectrum recorded at V s = −1.5 V; thus, we estimate that the onset of the excitonic STML is between −1.8 and −1.5 V. At V s = −1.8 V, overbias emission occurs at a photon energy about 0.2 eV higher than the quantum cutoff e|V s | = 1.8 eV, with clear evidence of neutral A exciton excitation. This inefficient overbias emission may be due to multielectronic processes [25,26]. All together, these observations are consistent with an STML excitation mechanism on hole injection in the valence of an n-doped semiconductor, which is described as channel 1 in Fig.…”
Section: Resultssupporting
confidence: 85%
“…These two peaks are not present (or cannot be distinguished from the background) in the spectrum recorded at V s = −1.5 V; thus, we estimate that the onset of the excitonic STML is between −1.8 and −1.5 V. At V s = −1.8 V, overbias emission occurs at a photon energy about 0.2 eV higher than the quantum cutoff e|V s | = 1.8 eV, with clear evidence of neutral A exciton excitation. This inefficient overbias emission may be due to multielectronic processes [25,26]. All together, these observations are consistent with an STML excitation mechanism on hole injection in the valence of an n-doped semiconductor, which is described as channel 1 in Fig.…”
Section: Resultssupporting
confidence: 85%
“…Recent studies of plasmonic light emission in tunnel junctions have reported a strong upconversion effect, with generated photon energy ( ℏω ) significantly above the energy threshold of the incident electrons ( eV , where V is the applied bias). While multiple processes can produce such above-threshold photons, recent work , has revealed the dominant role of LSP-induced hot carriers for this.…”
Section: Introductionmentioning
confidence: 99%
“…Photoemission detection in MJs also represents a powerful tool for determining charge transport mechanisms through molecules [102,103]. In this regard, Tefashe et al recently investigated symmetric SAM junctions consisting of Ru-(bpy) 3 oligomers of varying lengths sandwiched between conducting carbon contacts [104].…”
Section: Photoemission In Mjsmentioning
confidence: 99%